The Anisotropy Induced by a Magnetostriction in Exchange-Biased Two-Layer Films - Gomonay, O.V.; Lukyanchuk, I. (Металлофизика и новейшие технологии, 2014)
The exchange bias at ferromagnetic (FM)/antiferromagnetic (AF) interfaces strongly depends upon the state of antiferromagnetic layer, which is sensitive to mechanical stresses due to its strong magnetoelastic coupling. In a given paper, we consider magnetoelastic effects, which arise at FM/AF interface due to misfit of lattices and magnetic ordering. We show how magnetostriction affects mutual orientation of the AF and FM vectors as well as magnetic easy-axis direction in thin AF layer. The results obtained can be used for tailoring of exchange-biased systems. Величина обменного подмагничивания на границе раздела ферромагнетик (ФМ)/антиферромагнетик (АФ) существенно зависит от состояния антиферромагнитного слоя, который, благодаря сильным магнитоупругим взаимодействиям, чувствителен к механическим напряжениям. В данной статье рассмотрены магнитоупругие эффекты, возникающие на границе раздела ФМ/АФ из-за решёточного несоответствия и магнитного упорядочения. Показано, каким образом магнитострикция влияет на взаимную ориентацию АФ- и ФМ-векторов и на направление лёгкой оси в тонком АФ-слое. Полученные результаты могут быть использованы при создании систем с обменным подмагничиванием. Величина обмінного підмагнетовування на межі поділу феромагнетик (ФМ)/антиферомагнетик (АФ) істотно залежить від стану антиферомагнетного шару, який, завдяки сильним магнетопружнім взаємодіям, чутливий до механічних напружень. В даній роботі розглянуто магнетопружні ефекти, що виникають на межі поділу ФМ/АФ через ґратницеву невідповідність і магнетне впорядкування. Продемонстровано спосіб, в який магнетострикція впливає на взаємну орієнтацію АФ- і ФМ-векторів і на напрямок легкої осі в тонкому АФ-шарі. Одержані результати можуть бути використаними при створенні систем з обмінним підмагнетовуванням.